Evolution of the caecal epithelial barrier during Clostridium difficile infection in the mouse. Issue 8 (August 1989) - Heyman, M; Corthier, G; Lucas, F; Meslin, J C; Desjeux, J F
Abstract : The most striking effect of Clostridium difficile infection is its degrading of the intestinal barrier. The aim of this study is to establish whether the cellular or paracellular constituent of the barrier is the initial target of the toxins produced by C difficile. Accordingly, the caecal epithelium of C3H/He mice was challenged under three experimental conditions with the C difficile strain VPI 10463: (1) by in vivo inoculation of axenic mice, (2) by adding the toxins to ligated caeca in vivo, and (3) by adding them to the mucosal side of isolated caeca in Ussing chambers. Under all three conditions, the epithelial barrier was tested in caeca mounted in these chambers. The transepithelial potential difference (PD), electrical conductance (G), and intact and degraded Horseradish peroxidase (HRP) fluxes were used as indexes of permeability. Results were as follows: (1) In axenic mice, C difficile caused severe infection, produced toxins A and B, reduced PD, and enhanced G and intact HRP fluxes without changing degraded HRP fluxes, (2) four hours after the toxins were added to ligated caeca in vivo, PD was relatively unaltered, but G, and intact and degraded HRP fluxes increased, and (3) when toxins were added to caeca during two hours in the Ussing chambers, the only modification observed was an increase in degraded-HRP fluxes. These results indicate that the C difficile toxins gradually cause intestinal lesions. After an apparent resistance, they stimulate the endocytotic process and then increase paracellular permeability and finally cause loss of cell viability.